Preparation of Graphene Flakes and Studying Its Structural Properties - M. Al-Saadi , Tagreed; A.K. Jihad, Mustafa (Iraqi Journal of Science, 2023)
The grapheme Flakes were prepared by reduction graphite oxide which was prepared by Hummer’s method. X-ray diffraction (XRD) pattern showed that the graphene oxide have a sharp peak at (001) with d-spacing d001= 7.4Å at angle 2ϴ=11.85˚and graphene has broad peak at (002) with d-spacing d002=3.4Å at angle 2ϴ= 25.72˚ with lattice constant (a=2.47 Å). The particle size was calculated by using equation Debye - Scherer and Williamson - Hall equations, Scanning electron microscopy examination and particle size analyzer proved that the graphene Flakes were in nano size. Also the surface area of nanoparticles showed a value 270 m2/g . The micrographs of (scanning electron microscopy) showed that graphene oxide has a fluffy aggregation and the form of graphene as a flakes or nano-sheets.